Hukuman Tata Tertib sebagai Instrumen Penertiban dan Pemasyarakatan dan Rumah Tahanan Negara - Ainal Hadi (Kanun Jurnal Ilmu Hukum, 2014)
The effort of educating prisoners in the context of correctional system is still full of problems for example imposition of discipline and security of the correction and detention institutions. The annoyance of security and discipline and the escape of them threaten the education.  One of the instruments applied by the government is the Minister of Law and Human Rights Regulation Number 6, 2013 regarding the Correction and Detention Institutions Conduct containing the rules that must be obeyed by the prisoners and detainees along with the imposition of discipline punishment as an indicator to know whether their behavior is good or bad.  Discipline Punishment as An Enforcing Instrument and Imprisonment and Detention